Systemic food web reorganization due to multiple pressures in seven Baltic Sea sub-basins - Faithfull, Carolyn; Taylor, John M; Puntila-Dodd, Riikka; Ito, Maysa; Scotti, Marco; Calkiewicz, Joanna; Labuce, Astra; Margoński, Piotr; Ammar, Yosr; Müller-Karulis, Bärbel; Olin, Mikko; Putnis, Ivars; et al. (Oxford University Press, 2026)
The Baltic Sea ecosystem is highly impacted by multiple human induced pressures and climate change. Despite this, restoration actions are often directed towards individual measures, ignoring trade-offs and synergies that may affect multiple ecosystem processes and services. Due to the bathymetry of the Baltic Sea, sub-basins may be differently impacted by pressures, making it challenging to observe common patterns and co-occurring processes. Here, we provide the first comprehensive analysis of systemic spatiotemporal changes of food webs across seven Baltic Sea sub-basins. Our analyses cover 26–46 years of harmonized data collection and apply integrated trend analysis in seven sub-basins. We compare temporal trends of key structural food web components, focusing on relative changes between trophic guilds, and interpret these changes in relation to variations in key environmental factors and human pressures. We found shifts in trophic-guild balance and ecosystem reorganization in all sub-basins, which were associated with regional changes in human induced pressures. According to the EU Marine Strategy Framework criteria, this indicates poor food web status across all sub-basins. In some cases, the altered food web regimes have remained despite reductions in the pressures that contributed to the initial shift. Climate warming has played a role, in some cases exacerbating the effects of other human induced pressures. Our results underscore that coordinated actions to reduce pressures such as fishing and nutrient loading are needed to improve food web status in the Baltic Sea.
Keywords: integrated ecosystem analysis; fisheries; eutrophication; ecosystem-based management; good environmental status; climate change